The medicinal and culinary uses of herbs and spices (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2009)
Herbs and spices have been used for centuries as food flavoring and/or as alternative therapy for certain illnesses. According to the World Health Organization, almost 80% of the world population or close to four billion people use medicinal herbs for some aspects of primary health care. This presentation is a digest of our 400-page book which is a rediscovery of some 100 selected herbs and spices used by our ancestors. The information on herbs and spices provide updates with current knowledge through description of the plant and the parts used for culinary and medicinal purposes. Whenever analyzed by modern chemistry, the active constituents or components responsible for specific beneficial roles are identified. Market forms and commercial production, now available, are given including labeling and regulation of the products. Guidelines are also given for selecting, purchasing, and using them safely. Consumers should always consult their physicians before buying or taking any medicinal herb or any dietary supplement. For spices primarily used as food flavorings, nontoxic varieties should be consumed in the amounts traditionally used for palatability and safety. Examples from the 250 savory recipes that taste much better by adding several herbs and spices which are included in the book Herbs and Spices: Their Culinary and Medicinal Uses were shown.